1977
DOI: 10.1159/000212218
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on the Role of Aspartic Acid Racemization in the Aging Process

Abstract: Racemization of aspartyl residues in human dentine and enamel proteins has been shown to occur at a rate which corresponds to an enrichment in the D-aspartic acid content of 0.1 % per year. This rate can be used to calculate the ages of living people or the in vivo lifetimes of slowly turned over proteins. We present stereo chemical arguments for conformational changes in proteins as a consequence of racemized amino acid residues. In metabolically stable proteins, this phenomenon may play some part in the agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0
2

Year Published

1978
1978
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 5 publications
1
37
0
2
Order By: Relevance
“…In addition, there were many studies the relationship between extent of amino acid racemization and age in human teeth (Ohtani 1995b;Shimoyama & Harada 1984). They found high correlation of racemization and age that was consistent with results of another study by Helfman et al (1977). This suggested that amino acid racemization can be utilized for age estimation.…”
Section: History Of Age Estimation By Using Aspartic Acid Racemizationsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, there were many studies the relationship between extent of amino acid racemization and age in human teeth (Ohtani 1995b;Shimoyama & Harada 1984). They found high correlation of racemization and age that was consistent with results of another study by Helfman et al (1977). This suggested that amino acid racemization can be utilized for age estimation.…”
Section: History Of Age Estimation By Using Aspartic Acid Racemizationsupporting
confidence: 74%
“…They reported a relationship between concentration of D-aspartic acid and age in these tissues and particularly in dentine which is better correlate than enamel (r=0.979). The previous study (Helfman et al 1977) reported that aspartic acid racemization is a process which occurs in metabolically stable proteins of the mammalian body and amino acid within protein and are changed with increasing age. In addition, there were many studies the relationship between extent of amino acid racemization and age in human teeth (Ohtani 1995b;Shimoyama & Harada 1984).…”
Section: History Of Age Estimation By Using Aspartic Acid Racemizationmentioning
confidence: 99%
“…1B) and the nucleus (Fig. 1C) with the prediction that racemization of aspartyl residues would induce conformational changes in a protein, and these in turn could alter its physicochemical properties (9). Because HMW aggregates are thought to be precursors to the WI protein, the high D/L Asp ratio in the HMW fraction (Table 3) suggests that racemization precedes the formation of WI protein.…”
Section: Discussionmentioning
confidence: 83%
“…We have previously suggested that alterations in protein conformation will result from racemization of aspartyl residues (9). If racemization is to any degree responsible for the changes in the properties of lens proteins, then D-aspartic acid should…”
mentioning
confidence: 99%
“…Consequently, amino acid racemization is widely applied for age estimation in many tissues which comprise proteins. Furthermore, the relationship between amino acids racemization and age can be used for investigation of lifetime of protein ageing (Helfman et al 1977) and pathological diseases in older individuals (Powell et al 1992;Shapiro et al 1991). …”
Section: Amino Acid Racemizationmentioning
confidence: 99%